CALIDAD DE LAS ANOTACIONES DE ENFERMERÍA EN PACIENTES ATENDIDOS EN EL CENTRO QUIRURGICO DEL HOSPITAL REGIONAL DE ICA JULIO– DICIEMBRE 2016 - HERRERA FAJARDO, DARLENY MIRELLA (2016)
The present investigation titled as “Quality of the nursing annotations in patients attended in the surgical center of the Regional Hospital of Ica, July-December 2016”; The objective was to determine the quality of the annotations of the nursing annotation, in order to know in an updated way the quality of these records that represent a fundamental part of the work performed by the nurses who work in the surgical center of said institution. The results obtained will be used to develop optimization protocols, in addition to properly directing the training of personnel based on scientific evidence. The level of study was applicative, quantitative, with a deductive, retrospective cross-sectional method. The total population to be studied consisted of 159 nursing annotations, the technique chosen for the documentary analysis was through a validated checklist. As results, it was obtained that of 100% (159 medical records), 84.3% (134 medical records) were of poor quality and 15.7% (25 medical records) had aspects to improve. When evaluating the Structure dimension, it was seen that 48.4% (77 medical records) had a Satisfactory grade, while 39% still had to be Improved (62 medical records) and 12.6 (20 medical records) were classified as Deficient. Regarding the Content dimension, it was found that 100% had a deficient level. Based on the foregoing, it was concluded that the quality of nursing annotations in patients treated at the surgical center of the Regional Hospital of Ica from July to December are Deficient. Key Words: Quality, Nursing Notes, SOAPIE Method